HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN MORAL ANAK DI SD N 3 BUNTALAN KLATEN TENGAH, KLATEN - Piscolia Dynamurti Wintoro; Sri Wahyuni (INVOLUSI: Jurnal Ilmu Kebidanan, 2019)
The formation of the moral of a child who is in a period of development is influenced by the stimuli it receives. Whether or not a child's morale is influenced by the positives and negatives of the stimulus. The role of family, school and play environment is considered very influential in shaping children's morale. Parenting is closely related to children's moral development because parenting is a process of interaction between father and mother and child. This study aims to determine the relationship between parenting and moral development of children in SD N 3 Buntalan, Klaten Tengah, Klaten. This research method is descriptive correlational with cross sectional approach. The number of samples is 33 respondents with total sampling technique. The instrument used is the PAQ questionnaire for parenting and DIT for moral development. Data analysis using Kendall tau test. The results showed that the majority of parenting styles are democratic as many as 21 respondents (63.6%) and the moral development of children is conventional as many as 21 respondents (63.6%), p value 0.025 (p <0.05). The conclusion of this study is that there is a relationship between parenting styles with children's moral development in SD N 3 Buntalan, Klaten Tengah, Klaten. Suggestions for parents are expected to be able to apply democratic parenting that is not too hard and does not impose their will on their children.